Inclusion relations between classes of hypergeometric functions. (1994) - Ahuja, O. P.; Jahangiri, M.
Abstract : The use of hypergeometric functions in univalent function theory received special attention after the surprising application of such functions by de Branges in the proof of the 70-year old Bieberbach Conjecture. In this paper we consider certain classes of analytic functions and examine the distortion and containment properties of generalized hypergeometric functions under some operators in these classes.